Psikoedukasi Pendidikan Seks Pada Murid Sekolah Dasar - Ahmad Ariffadilah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Abstract: The community engagement program aims to provide psychoeducational sessions on Sex Education to elementary school students, enabling them to recognize potential dangers, reject unwanted advances, and seek help when needed. This knowledge is expected to empower children to protect themselves from the threat of sexual harassment. Thirty students from SDN 1 Dewantara participated in the program, which covered topics such as body parts, boundaries, and potential risks. The program employed a Psychoeducation approach, utilizing visual aids such as images, animated videos, and quiz games. The outcomes revealed that the psychoeducational program significantly enhanced students' understanding of the subject matter. Additionally, it contributed to their comprehension and awareness of the importance of Sex Education, equipping them to effectively navigate situations and prevent potential instances of sexual harassment. The positive feedback and support from stakeholders, including the school principal, teachers, and students, underscored the success of the initiative. This community engagement program effectively conveyed the significance of Sex Education to elementary school students, recommending its implementation to offer enhanced protection against sexual harassment and provide a strong foundation for understanding gender differences and puberty-related changes.